Animal Locomotion (1968)
24 frames showing harness racing horse in motion.
Photo copyrighted by Eadweard Muybridge.
This record contains unverified, old data from caption card.
Caption card tracings: Horse racing--Harness races--1887; Animal and human locomotion; Motion pictures; Shelf.
Keywords: Animal locomotion -- 1880-1890.